Dear DTCA, Please Don’t Deceive Me, Don’t Play on My Fantasy - Bélisle-Pipon, Jean-Christophe (BioéthiqueOnline, 2016)
In the face of drugs advertising, what can we do? Is Direct-to-Consumer Advertising (DTCA) designed to be beneficial by objectively presenting a product or are they rather seeking to convince us that their product is patently good? Through this song, the goal is to live the experience of a patient who is subject to drug advertising, by integrating into the stanzas the main ethical issues raised by advertising.